Autophagy inhibits C2-ceramide-mediated cell death by decreasing the reactive oxygen species levels in SH-SY5Y cells. (9th June 2017) - Fan, Chenghe; Liu, Yuanyuan; Zhao, Mingming; Zhan, Rui; Cui, Wei; Jin, Haiqiang; Teng, Yuming; Lv, Pu; Zheng, Lemin; Huang, Yining
Highlights: C2-ceramide induces caspase-3-independent SH-SY5Y cell death. C2-ceramide induces autophagy through ERK1/2 pathway in SH-SY5Y cells. Autophagy inhibits C2-ceramide-induced SH-SY5Y cell death by decreasing ROS production. Abstract: Ceramide has been recognized as a second messenger that regulates several intracellular processes in neuronal cells. However, its role in neuronal autophagy is not fully understood. In this study, we used a human neuroblastoma cell line (SH-SY5Y) to investigate the mechanisms underlying C2-ceramide-mediated cell death and autophagy. C2-ceramide induced caspase-3-independent cell death. In addition, C2-ceramide induced autophagy, decreased the activation of Akt and mTOR, and increased the activation of JNK and ERK1/2. However, only inhibition of ERK1/2 with PD98059 prevented C2-ceramide-induced autophagy, indicating that the ERK1/2 pathway contributes to ceramide-induced autophagy. According to the results of the flow cytometric assays, C2-ceramide-induced cell death was increased by 3-methyadenine (3-MA) and decreased by rapamycin. Furthermore, the generation of reactive oxygen species (ROS) in the cells was increased by 3-MA and decreased by rapamycin. Based on these datas, autophagy protected SH-SY5Y cells from C2-ceramide-induced cell death by decreasing ROS production. Therapeutic strategies that regulate autophagy may be used in the treatment of neurological disorders associated with ceramide-induced cell death.